Mechanism study for directivity of TR probe when applying Eddy current testing to ferro-magnetic structural materials. (September 2021) - Zhang, Shurui; Uchimoto, Tetsuya; Takagi, Toshiyuki; Hashimoto, Mitsuo; Takeda, Sho
Abstract: Transmitter/receiver (TR) pancake probes are widely used in eddy current testing (ECT) owing to their multi-axial structure and sensitivity in different directions. However, the behavior of the ECT signal affected by the directivity of the TR pancake probe has not been discussed, especially when considering the magnetic properties of materials. The present paper therefore investigates the behavior of the ECT signal for different angles between the crack orientation and the centerline of the probe in experiments and numerical analysis. In experiments, sample plates of ferromagnetic carbon steel SM490 and non-ferromagnetic stainless steel AISI316 are employed for the investigation. Slits are fabricated on the plates to simulate cracks. Numerical analysis adapts a finite element method, the A r method. The change in signal amplitude with the scanning angle has an obvious difference between the two materials in both experimental and simulation results. The presence of magnetic flux leakage around a slit in ferromagnetic material is assumed as the main reason for the difference and subsequently examined in numerical analysis. The results reveal that the magnetic field detected for a ferromagnetic material is the superposition of the magnetic field induced by eddy current and the magnetic flux leakage. The present study confirms the presence of magnetic flux leakage and explains the difference in the directivity of a TR pancake probe between ferromagnetic and non-ferromagnetic materials. This work contributes to a more reasonable analysis of ECT signals measured using a TR pancake probe when detecting cracks in different materials and the evaluation of crack orientation.